THE EFFECT OF PROVIDING GAMAL LEAF SILAGE (GLIRICIDIA SEPIUM) ON CONSUMPTION,WEIGHT GAIN AND RANSUM CONVERTION OF LOCAL MALE GOATS DERIVED FROM ETTAWA CROSSBREEDS - Ridha, Ahmad; Yustendi, Dedhi; Daniel, Daniel; Zulkifli, Zulkifli (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study aimed to evaluate the effect of gamal (Gliricidia sepium) leaf silage on the growth performance of local male goats. The research focused on key growth parameters, including daily feed consumption, daily body weight gain (PBBH), feed conversion, and feed efficiency. Method: The experiment was conducted using a randomized block design (RAK) with four treatments and four replications. The treatments included (P0) control with elephant grass without gamal leaves, (P1) 20% gamal leaf silage and 80% elephant grass, (P2) 50% gamal leaf silage and 50% elephant grass, and (P3) 100% gamal leaf silage. The goats were monitored over four weeks to assess their growth response to different feeding compositions. Results: The findings revealed a significant effect of gamal leaf silage on the growth performance of local male goats. The inclusion of gamal leaf silage improved daily body weight gain, feed conversion, and feed efficiency. Higher proportions of gamal leaf silage in the diet resulted in better growth performance compared to the control group. Novelty: This study highlights the potential of gamal leaf silage as an alternative, cost-effective feed source for ruminants. The results contribute to the understanding of utilizing non-conventional feed ingredients to reduce feed costs while maintaining livestock productivity.